Precision Emotion and Affective Context (PEAC) process model: a theoretical framework for creating the affective circumstances that promote engagement - Carpenter, Stephanie M.; Roberts, Nicole A. (Frontiers in Psychology, 2025)
Behavior change interventions are key to improving health and well-being. Knowledge of appropriate health behaviors does not, however, translate into engaging in them. We propose the “Precision Emotion and Affective Context (PEAC) Process Model of Engagement for Behavior Change” to serve as a theoretical framework to advance our understanding of how affect drives engagement and subsequent behavior change. Our framework highlights the importance of accounting for affective circumstances when designing and implementing behavior change interventions. The model accounts for affect that is both incidental and integral to the intervention: ongoing affective states that may work for or against the likelihood of engaging with the intervention (incidental), and affective states that are elicited by the intervention and consequently shape behavior change (integral). We focus on the promise of moderate levels of arousal and positive affective states, along with the need for contextual congruence, social acceptability, and personally meaningful approaches, for enhancing the likelihood of engagement and positive behavior change in interventions. Finally, just-in-time intervention approaches are discussed as a means of delivering personalized, affectively informed interventions that leverage advances in digital health technologies to promote opportunities for real-time implementation. This theoretical framework thus serves as a guide for constructing or harnessing the affective circumstances necessary to promote sustained intervention engagement and behavior change.